ESTUDO EPIDEMIOLÓGICO DO ÍNDICE DE COINFECÇÃO POR LEISHMANIOSE VISCERAL E HIV NO BRASIL, 2009-2024 - Cobra França , Marina; Ferreira da Cunha Santos , Mirella; Gonzales Gouveia , Juceli; Antero , Leandro (ANAIS DO ENIC, 2026)
-